Communication plan based on information and communication technologies for Peruvian university organizational culture - Otiniano Castillo, Lorella Priscila (2025)
The research proposes a communication plan based on ICT for Peruvian university organizational culture, employing a basic methodology with an interpretative paradigm, qualitative approach, and phenomenological and hermeneutic design. Ten experts and twenty university representatives served as informants, alongside various management documents and other audiovisual and advertising sources. Techniques for gathering information included semi-structured interviews, document analysis, and discourse analysis. Results indicated that while the university possesses digital tools, platforms, and channels, the daily information released is repetitive, lacking image management and a digital strategy for stakeholder interaction. This highlights the need for a communication plan focused on active listening, closeness, and interaction to minimize uncertainty and build the brand, selecting the necessary technological tools and digital platforms for effective communication and strengthening organizational culture. Ultimately, it concludes that integrating tangential aspects can propose a communication plan that offers a valuable contribution in the corporate field, helping to define the university's significance in disseminating institutional strategic values as part of its organizational culture, positively impacting its market position and solidifying its educational quality, thus creating a replicable experience.